On Grouped Observations and Adjacent Aspects of Statistical Theory - Gjeddebæk, N. F. (Methods of Information in Medicine, 1963)
The present paper is intended to provide a review of some aspects and difficulties of statistical theory and its practical applicability. As the non-parametric theory particularly needs support, the author has tried to transfer to it ideas from the theory of grouped observations, which seem beneficial to non-metric cases.The statements rendered about the three quantum mechanical models showing that these models are in some way of equal plainness will perhaps be considered advantageous to this particular field of science.Die vorliegende Arbeit beabsichtigt, eine Übersicht über einige Aspekte und Schwierigkeiten der statistischen Theorie und ihrer praktischen Anwendbarkeit zu geben. Da besonders die nichtparametrische Theorie einer Stütze bedarf, wird versucht, diejenigen Gedanken aus der Theorie der gruppierten Beobachtungen, die für nichtmetrische Fälle brauchbar erscheinen, auf die erstere zu übertragen.Die Darlegungen über die drei quantenmechanischen Modelle zeigen, daß diese Modelle in gewisser Hinsicht gleich einfach sind; sie können vielleicht für dieses spezielle Gebiet von Nutzen sein.